MODERN ASPECTS OF METABOLIC SYNDROME IN CHILDREN - Kholmuradova Zilola Ergashevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. In recent years, there has been a clear trend of steady growth and spread of metabolic syndrome (MS) among the population of developed countries, including in Uzbekistan [3,20]. Thus, according to multicenter international studies, the spread of MS among the adult population varies from 10 to 40% [2,16], forming the main causes of mortality in the adult population. Thus, according to WHO (2006), in the proportion of 10 main risk factors for overall mortality, the three leading places are occupied by the components of the metabolic syndrome: arterial hypertension, high blood cholesterol, high body mass index. The whole importance of the problem lies in the fact that more and more often we have to deal with this problem in children and adolescents, because it is in childhood that the origins of the metabolic syndrome are recorded later in adults. [12,13,14]. Thus, the prevalence of MS in childhood varies according to different authors from 4% to 28.7% in the general population and is significantly higher among obese children and adolescents [5,6,7,8]. Despite the difference in methodological approaches, clinical and epidemiological studies indicate a steady increase in the prevalence of MS among adolescents and young people [9,10,11], which was confirmed by long-term studies in US adolescents, which showed an increase in the incidence of MS over the past 10 years from 4.2% to 6.4% in the population. For the first time the term "metabolic syndrome" was introduced by Reaven G.M. (1988) [15,16] who combined under this name the syndrome of insulin resistance (IR), arterial hypertension (AH), dyslipidemia, type 2 diabetes mellitus, and obesity. This served as a further comprehensive study of it in the adult population, and for a long time, this problem has become relevant for pediatricians. Numerous discussions held by pediatricians in recent years prove the priority of one or another symptom as the leading symptom of MS in children and adolescents. One of the serious trends has been the consideration of obesity, namely its visceral-abdominal form, as a key syndrome-forming component of MS. The choice of obesity as one of the reasons for the development of MS is not accidental. This modern world trend is based on significant factors. The first group of factors includes numerous data proving a significant, often key role of obesity in the formation of both individual signs that make up MS and the syndrome itself. So it is known that up to 90% of patients with DM2, which is the main, "large" component of MS, are obese [6,7,10,1].